Genome-wide variation in the distribution of transposable and repetitive elements in the Western Clawed Frog (Silurana tropicalis) - Shen, Jiangshan J. (My University, 2011)
Repetitive elements, including tandem repeats and transposable elements (TE), are genetic features of all plant and animal genomes. Despite their abundance and the phylogenetic breadth of host genomes, factors that control the genome-wide distribution of repetitive elements are not well understood. Here we have evaluated the correlation between various genomic predictor variables such as gene expression level, distance from genes, and GC content, with the presence of TEs and non-TE repeats in two kilobase windows of the complete genome sequence of the Western Clawed Frog (Silurana tropicalis). We found that the distributions of different classes of TEs and repeats have distinct correlations with these predictor variables, including a generally strong negative correlation with proximity to exons and GC content. We also found that DNA transposons, but not retrotransposons, are preferentially inserted or preferentially retained near germline-expressed genes. Retrotransposons and simple repeats are found more often in or near conserved regions than expected by chance. These results offer insights into various models that have been proposed to account for heterogeneity in the genomic distribution of repetitive elements, most notably for the “gene disruption model” which posits that TE insertion and repeat presence near or in genes imposes costs to host fitness. In general, multiple lines of evidence suggests that the nature of natural selection on TE and other repetitive element evolution in this frog appears to be similar to that acting on TE and other repetitive elements in the human genome. This is possibly related to the similar size and level of complexity of the genomes of both of these species.
Keywords: genome evolution; natural selection; African Clawed Frogs; gene expression; GC content; Genetics and Genomics; Genetics and Genomics